2013
DOI: 10.1093/toxsci/kft258
|View full text |Cite
|
Sign up to set email alerts
|

Utility of B-13 Progenitor-Derived Hepatocytes in Hepatotoxicity and Genotoxicity Studies

Abstract: AR42J-B-13 (B-13) cells form hepatocyte-like (B-13/H) cells in response to glucocorticoid treatment. To establish its utility in toxicity and genotoxicity screening, cytochrome P450 (CYP) induction, susceptibility to toxins, and transporter gene expression were examined. Conversion to B-13/H cells resulted in expression of male-specific CYP2C11 and sensitivity to methapyrilene. B-13/H cells constitutively expressed CYP1A, induced expression in response to an aryl hydrocarbon receptor agonist, and activated ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(71 citation statements)
references
References 52 publications
(71 reference statements)
2
69
0
Order By: Relevance
“…5 B and C demonstrate that methapyrilene exposure resulted in phospholipidosis in both B-13 and B-13/H cells in dose-dependent manners, most potently in B-13 cells. As previously reported ( Probert et al, 2014 ), methapyrilene was only toxic to B-13/H cells and not to B-13 cells and similar results were observed in these studies ( Fig. 5 D).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…5 B and C demonstrate that methapyrilene exposure resulted in phospholipidosis in both B-13 and B-13/H cells in dose-dependent manners, most potently in B-13 cells. As previously reported ( Probert et al, 2014 ), methapyrilene was only toxic to B-13/H cells and not to B-13 cells and similar results were observed in these studies ( Fig. 5 D).…”
Section: Resultssupporting
confidence: 92%
“…5 D). Previous work has also demonstrated that methapyrilene hepatoxicity is inhibited by sulfhydryl reducing agents and the Ca 2+ channel blocker nifedipine ( Ratra et al, 1998a , Probert et al, 2014 ). Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The transdifferentiated rat B13/H cell system has been reported to express a range of constitutive and inducible drug metabolising enzymes, such as the Cyp enzymes (Probert et al 2014). Therefore the hepatocyte-like B13/H cells were subsequently treated with PB (2mM) for up to 9 days, with the treatment and media replenished every 72 h. Analysis of the treated cells demonstrated significant increases in Cyp2b1 mRNA ( Figure 2A) and Cyp2b activity across the 9 days ( Figure 2B).…”
Section: Phenobarbital Treatmentmentioning
confidence: 99%
“…It was reported by Shen et al, (Shen et al 2000) that treatment of the undifferentiated B13 cell with dexamethasone for two weeks stimulated the cell to transdifferentiate into hepatocyte-like B13/H cells. The differentiated cell population display gene expression profiles similar to primary hepatocytes and can be maintained in culture for considerably longer than primary hepatocytes without de-differentiation (Probert et al 2013;Probert et al 2015), making them a useful model for the proposed treatments here.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, qPCRbased CARCINOscreen ® evaluation can be made by comparing the expression ratios of any of the four predictive genes with the threshold values. With regard to the four selected predictive genes for qPCR, Abcb1b is a member of the ATP-binding cassette (ABC) protein superfamily and multi-drug resistanceassociated protein, and the protein transporter is reported as being functional in B-13/H cancer cells (Probert et al, 2014). Merrick et al (2012) reported that administration of the hepatocarcinogen aflatoxin B1 (AFB1) to male F344 rats significantly increased the expression of Abcb1b in the rat liver.…”
mentioning
confidence: 99%